Students' Disciplinary Behavior at Senior High School in Complying with School Rules - Halila Istigfaroh; Ahmad Riza; Aisyah Lubis; Edea Mecca Safitri; Gracia Tiurmauli Purba; Mamluatul Khoiriyah; Micheal Junior; Selvia Azzahra; Rizky Dinda Sarmita Harahap; Hambali Hambali (Journal of English Language and Education, 2026)
This study aims to describe the role of school regulations in shaping student discipline at SMAN 15 Pekanbaru. This study shows that school regulations play a significant role in shaping student discipline at SMAN 15 Pekanbaru. Through the implementation of clear rules, teacher supervision, and the provision of sanctions and coaching, students are encouraged to practice orderly and responsible behavior. Although various violations, such as lateness, incomplete use of attributes, and other rule violations, the implementation of the regulations has generally been running well. The research method used is descriptive qualitative with data collection techniques through observation and interviews with two teachers and 42 students. The results of this study indicate that the effectiveness of discipline depends not only on the sanctions given, but also on student self-awareness, teacher role models, and support from the school environment. Therefore, consistent supervision and a more humanistic approach between teachers and students are needed so that the values of discipline can be deeply ingrained. Thus, school regulations not only function as a tool for controlling behavior, but also as a means of character formation that prepares students to become responsible individuals who are ready to face life in the future.